2020
DOI: 10.1001/jamanetworkopen.2020.24329
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neighborhood Deprivation With Epigenetic Aging Using 4 Clock Metrics

Abstract: Key Points Question Is living in a neighborhood with a high concentration of household and population features characteristic of lower socioeconomic status (ie, a neighborhood with high deprivation) associated with epigenetic age acceleration across first- and second-generation clock metrics? Findings This cross-sectional study comprised 2630 women who had a sister with breast cancer but had not had breast cancer themselves. Those living in areas with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 59 publications
4
75
0
1
Order By: Relevance
“…2019 ) and physical activity and neighborhood SES in cross-sectional analyses of 2,700 women in the United States ( Kresovich et al. 2020 ; Lawrence et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…2019 ) and physical activity and neighborhood SES in cross-sectional analyses of 2,700 women in the United States ( Kresovich et al. 2020 ; Lawrence et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We encourage researchers to outline and differentiate the role of racism and not ancestry among these biomarkers. This is particularly important given the reported associations of epigenetic aging with social factors including diet [13,27], racial discrimination [28], neighborhood deprivation [29], and violence [30]. This study has some important limitations including small sample size and limited generalizability given that the cohort was comprised of only Polish women.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in the Multi-Ethnic Study of Atherosclerosis (MESA) study, neighborhood characteristics have been found to in uence DNA methylation of genes involved in stress response and in ammation (32). More interestingly, using newly developed epigenetic clocks based on DNA methylation, Lawrence et al recently reported that residing in a neighborhood with a higher deprivation index had higher epigenetic age acceleration estimated by Hannum, PhenoAge, and GrimAge clocks (33).…”
Section: Discussionmentioning
confidence: 99%